The Anatomical and Evolutionary Impact of Pain, Pleasure, Motivation, and Cognition: Integrating Energy Metabolism and the Mind-Body BERN (Behavior, Exercise, Relaxation, and Nutrition) Framework - Stefano, George B; Buttiker, Pascal; Michaelsen, Maren M; Esch, Tobias (International journal of molecular sciences, 2025)
In this manuscript, we highlight the evolutionary origins of mitochondria from bacterial endosymbionts and explore their contributions to health, energy metabolism, and neural-immune communication. Mitochondrial adaptability and the roles played by these organelles in promoting oxygen-dependent ATP production provide critical regulation of cognition, motivation, and inflammation. Hypoxia has been identified as an important initiator of inflammation, neurodegeneration, and mitochondrial dysfunction, emphasizing the overall importance of oxygen homeostasis to health and well-being. The Behavior, Exercise, Relaxation, and Nutrition framework highlights these observations as tools that can be used to optimize mitochondrial efficiency. Interestingly, mitochondrial dysfunction may also be linked to psychiatric disorders (e.g., schizophrenia), a hypothesis that focuses on energy dynamics, a proposal that may extend our understanding of these disorders beyond traditional neurotransmitter-focused concepts. Collectively, these perspectives underscore the critical contributions of mitochondria to health and disease and offer a novel framework that may help to explain the connections featured in mind-body medicine.
Keywords: Humans; Mitochondria; radost; zvířata; Exercise; motivace; Biological Evolution; kognice; mitochondrie; energetický metabolismus; Energy Metabolism; cvičení; biologická evoluce; bolest; Animals; Cognition; lidé; Motivation; Pleasure; Pain